The Epstein-Barr virus immortalizing protein EBNA-2 is targeted to DNA by a cellular enhancer-binding protein. - Ling, P D (1993)
The Epstein-Barr virus nuclear antigen EBNA-2 is essential for Epstein-Barr virus-induced immortalization of B cells. EBNA-2 is a transcriptional activator capable of modifying the expression of specific viral and cellular genes. However, the mechanism of EBNA-2 transactivation has been an enigma. We used a fractionated extract of CA46 lymphoblastoid cells and bacterially expressed EBNA-2 polypeptides to demonstrate that EBNA-2 is targeted to the Epstein-Barr virus latency C promoter (Cp) through interaction with a cellular DNA binding protein designated Cp binding factor 1 (CBF1). A glutathione S-transferase-EBNA-2 fusion protein containing aa 252-425 of EBNA-2 interacted with CBF1 to yield a slowly migrating complex in an electrophoretic mobility shift assay. Mutation of EBNA-2 aa 323 and 324, which lie within a highly conserved amino acid motif, abolished the interaction with CBF1. This same mutation also abolished the ability of EBNA-2 to activate the Cp in a cotransfection assay. The binding site for CBF1 was localized to residues -359 to -388 of the Cp by using an electrophoretic mobility shift assay and DNase I footprinting. Introduction of multiple copies of the CBF1 binding site upstream of a minimal heterologous promoter conferred EBNA-2 responsiveness on that promoter. Mutation of a core sequence CNGTGGGAA abolished CBF1 binding, and the mutated sequence was unable to mediate EBNA-2 transactivation. The CBF1 core sequence also occurs in other EBNA-2-responsive promoters suggesting that CBF1 may mediate EBNA-2 transactivation of both cellular and viral targets.